The Specificity of the Plot and Structure of the Buryat Fairy Tales (2018 field materials) - Badma-Khanda B. Tsybikova (Studia Litterarum)
The article is based on the results of the expedition research in 2018. It examines oral prose records of Chinese Buryats. The most impressive volume of these records includes the texts of fairy tales performed by Sebeenei Nordoboy Erdeni who is a local historian, an enthusiast for collecting oral creative art of Buryats. Twenty-nine fullfledged fairy tales have been recorded from him. The essay systematizes and groups into tentative blocks tales with a developed plot and detailed structural elements. The main principle of the fairy tales classification is the function of main character. Based on this principle, I classify the available material as the following six categories: heroic fairy tales, magic-fiction fairy tales, short stories, domestic fairy tales, cumulative fairy tales, and fairy tales containing mythological elements. Recorded from a talented shenekhen performer, this story-themed fund of fairy tales has variety and contains complete texts with artistic merits. The analysis made it possible to draw a conclusion: recorded in 2018, the oral prose of the Buryats of Inner Mongolia of the PRC, mainly represented by fairy tales, goes back to the traditional folklore of the Buryat ethnic group. The original performance of fairy tales and their main plot basis have not undergone any significant transformation. This instance was facilitated by several objective factors. One of them is that the Chinese Buryats, who found themselves isolated from the mother ethnic group, consciously, or perhaps unconsciously, chose to keep a traditional way of life in a closed ethnic circle.